2020
DOI: 10.1158/0008-5472.can-19-1991
|View full text |Cite
|
Sign up to set email alerts
|

Rare BRIP1 Missense Alleles Confer Risk for Ovarian and Breast Cancer

Abstract: Germline loss-of-function mutations in BRCA1 interacting protein C-terminal helicase 1 (BRIP1) are associated with ovarian carcinoma and may also contribute to breast cancer risk, particularly among patients who develop disease at an early age. Normal BRIP1 activity is required for DNA interstrand cross-link (ICL) repair and is thus central to the maintenance of genome stability. Although pathogenic mutations have been identified in BRIP1, genetic testing more often reveals missense variants, for which the imp… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(41 citation statements)
references
References 47 publications
2
27
0
Order By: Relevance
“…It was previously associated with breast cancer risk [76][77][78][79] however, results from these studies are inconsistent and several other studies found no association of BRIP1 mutations and breast cancer risk [80,81]. It is one of the most common OvC susceptibility genes with 0.9-2.5% frequency in all patients carrying a mutation in this gene [62,[82][83][84]. A study from Weber-Lassalle et al on the loss of function BRIP1 mutations found that these mutations confer a high OvC risk in familial OvC patients as well as in late-onset OvC patients (OR = 20.97 and 29.91 respectively) [83].…”
Section: Main Molecular Hallmarks Of Ovarian Cancer and Association Wmentioning
confidence: 99%
“…It was previously associated with breast cancer risk [76][77][78][79] however, results from these studies are inconsistent and several other studies found no association of BRIP1 mutations and breast cancer risk [80,81]. It is one of the most common OvC susceptibility genes with 0.9-2.5% frequency in all patients carrying a mutation in this gene [62,[82][83][84]. A study from Weber-Lassalle et al on the loss of function BRIP1 mutations found that these mutations confer a high OvC risk in familial OvC patients as well as in late-onset OvC patients (OR = 20.97 and 29.91 respectively) [83].…”
Section: Main Molecular Hallmarks Of Ovarian Cancer and Association Wmentioning
confidence: 99%
“…BRIP1 p.P47A, originally identified in a breast cancer patient and used as a negative control in our study, is also helicase-deficient (Cantor et al 2004). A recent study evaluated 18 additional BRIP1 missense mutations identified in ovarian and early-onset breast cancer patients for protein stability and effects on cell growth, cell cycle progression, and chromosome breakage in the presence of DNA damaging agents (Moyer et al 2020). Thirteen of these mutations were null or depleted in one or more of these functions, whereas five had fully normal function.…”
Section: Discussionmentioning
confidence: 99%
“…All BRIP1 truncating alleles yield loss of the helicase domain and are likely to lead to loss of protein (Levitus et al 2004;Levitus et al 2005;Levran et al 2005;Litman et al 2005;Steinberg-Shemer et al 2019). Missense alleles, which may retain at least partial protein expression and function (Levitus et al 2005;Bharti et al 2018;Moyer et al 2020), may cause a less severe phenotype. A recent analysis of genotype-phenotype associations in Fanconi anemia found an increased frequency of congenital abnormalities in patients with null genotypes compared to those with hypomorphic genotypes, suggesting that phenotypic severity may be influenced by the type of mutation (Fiesco-Roa et al 2019), although other studies have found conflicting results (Faivre et al 2000;Castella et al 2011;Steinberg-Shemer et al 2019).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the genetic linkage of DNA helicase defects to rare chromosomal instability disorders has been emphasized in this section, it should be stated that there are numerous studies documenting mutations in DNA helicase genes as being associated with cancers [400]. For example, a recent study established that rare missense alleles of BRIP1/FANCJ confer risk for breast as well as ovarian cancer [401]. This work is consistent with a previous study that truncating mutations in BRIP1/FANCJ confer susceptibility to breast cancer [402].…”
Section: Helicase Mutations and Predisposition To Cancermentioning
confidence: 99%